Research and Application of Wheel/Rail Adhesion Properties of High-speed Train in Frigid Area - CHEN Zheming; YU Yang; ZHANG Junling (机车电传动)
In order to grasp the wheel/rail contact state in frigid area harsh conditions and ensure the safe of the train’s operation, this paper studied the wheel/rail contact adhesion properties of the high-speed train which could reach 400 km/h in frigid area, in Russia. The related vehicle dynamics model and the wheel/rail rolling contact model were established. On the basis of above, the main influence factor of wheel/rail contact adhesive coefficient in frigid area was researched, and the correlative peak of adhesion curve and adhesion surface was obtained. Combined with project, under the premise of good wheel/rail contact state and with full use of adhesion conditions, the braking deceleration curve of the train was designed and verified with the correctness, rationality and validity.